Homicides Disguised as Fire Deaths - Žiūkaitė, Gabrielė; Jasaitė, Marta; Chmieliauskas, Sigitas; Vasiljevaitė, Diana; Laima, Sigitas; Banionis, Dalius; Stasiūnienė, Jurgita (Acta medica Lituanica, 2023)
Background: When conducting a forensic examination of burnt bodies, it is important to determine whether the victim was exposed to fire while alive or after death. The differential diagnosis between antemortem and postmortem burning is difficult and often cannot be made based on information obtained solely from the autopsy. The aim of the study is to review current literature on this topic and present clinical cases that illustrate how challenging the determination of vitality during the fire and manner of death can be. Materials and methods: We present four cases of burnt homicide victims, illustrating the complexity of forensic determination of the cause of death in the fire and the importance of differential diagnosis of antemortem and postmortem exposure to flames. Results: In the forensic assessment autopsy is a fundamental to determine the cause of death. When death is related to fire, particular findings during autopsy can help to suspect that the victim was alive. One of the main antemortem signs is the deposition of soot in the respiratory tract. Another important test is the toxicological analysis, which determines the level of carboxyhaemoglobin in the blood: a concentration of more than 50% indicates that the person died in the fire. Conclusions: Forensic examination of burnt bodies requires a comprehensive and detailed assessment of all available data. The autopsy, together with additional diagnostic forensic methods, including histological examination, toxicological analysis and postmortem computed tomography, allows the exact cause of death to be determined.